A continuum damage model for composite laminates: Part III - Fatigue. (February 2021) - Llobet, J.; Maimí, P.; Essa, Y.; Martin de la Escalera, F.
Abstract: The mesoscale continuum damage model for laminated composites that has been developed for the past 10 years at AMADE research group is extended for fatigue life and residual strength predictions. The same intra-laminar damage mechanisms are considered by means of the LaRC04 failure criteria, but a new set of functions are introduced to account for the degradation of the material under fatigue loads. The cycle jump approach is adopted within the finite element code to reduce the computational cost. In the follow-up paper part IV (Llobet et al., submitted for publication), the computational model is validated by simulating the progressive failure mechanisms of open-hole and double-edge notched specimens under static, tension-tension fatigue and residual strength load cases. All the experimental data is also described in detail in the accompanying part. Highlights: Composite laminates experience a degradation of the stiffness and strength under fatigue loading conditions. . Fatigue loads activate damage mechanisms that do not occur under static loads. . A new set of functions are introduced into the constitutive model to account for fatigue degradation. A cycle jump algorithm is introduced into the finite element code to improve the computational performance.